Synthesis and Characterization of Janus fenugreek Seed Gum-based Film for Food Packaging and Wound Dressing Applications - Bhattarai, Susmita; Khanal, Kalpana; Karki, Nirmal; Shahi, Dikpal Kumar; GC, Rajendra Bahadur; Bhatt, Lok Ranjan; Bhattarai, Narayan; Joshi, Mahesh Kumar (Journal of Nepal Chemical Society, 2024)
The use of plant-derived natural gum polysaccharides in food packaging and biomedicine is growing due to their biocompatibility, biodegradability, film-forming ability, abundant functional groups, and potential for chemical or physical modification to develop novel materials. In this study, fenugreek (Trigonella foenum-graecum) seed gum (FSG)-based Janus films with glycerol (GLY) as a plasticizer in varying concentrations (2%, 5%, 7%, and 10% w/w) were synthesized for potential food packaging and biomedical applications. The glycerol concentration significantly affected the stability, microstructure, moisture content, and solubility of the film, with 5% GLY yielding the most stable films. The water solubility was gradually increased with increasing the GLY content in the film sample. The film exhibited strong radical scavenging activity against DPPH assays, with an IC50 value of 158.73±0.013 µg/mL. The total phenolic content (TPC) and total flavonoid content (TFC) of the film were found to be 88.21±0.012 mg/g in gallic acid equivalents (GAE) and 9.36±0.018 mg/g in quercetin equivalents (QE), respectively. The pristine FSG film exhibited antibacterial activity against Staphylococcus aureus, Escherichia coli, and the fungal strain Candida albicans, which was significantly enhanced by incorporating the antibacterial drug penicillin. Additionally, we examined the impact of different films on chicken meat and cheese by monitoring changes in weight loss, color, pH, total aerobic mesophilic counts (TAMC), and psychrotrophic bacterial counts (PBC) during storage. Our results demonstrated that the samples packaged with pristine FSG film exhibited significantly lower TAMC and PBC values and slowed down the increase in pH values compared to the control samples, which further decreased by incorporating antimicrobial drug. These findings indicated that the Janus pristine FSG film is suitable for food packaging. Further, antimicrobial drugs incorporated into FSG film could be potential candidates for wound dressing applications.